2023
DOI: 10.1021/acsanm.2c04342
|View full text |Cite
|
Sign up to set email alerts
|

Role of CsMnCl3 Nanocrystal Structure on Its Luminescence Properties

Abstract: Cesium manganese chloride (CsMnCl 3 ) nanocrystals (NCs) have recently been recognized as potential lead-free perovskite candidates for red emission. To ascertain how the luminescence properties depend on the NC structures formed under different synthesis conditions, we synthesized CsMnCl 3 NCs in two polymorphic structures, namely, cubic (c-CsMnCl 3 ) and rhombohedral (r-CsMnCl 3 ), by tuning the reaction temperature of a hot injection route. c-CsMnCl 3 NCs are found to be nonemissive, whereas r-CsMnCl 3 NCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The r Mn2+ = 0.80 Å is very close to the r Zn2+ = 0.74 Å, which indicates the possible substitution of Zn 2+ ions in the lattice of Cs 12 Zn 4 Cl 20 . [ 19,20 ] Compared to the XRD pattern of undoped sample, the diffraction peaks are slightly skewed to the smaller angle side, which may be due to the introduction of Mn 2+ ions into the lattice. [ 16,21,22 ] The typical Cs 12 Zn 4 Cl 20 matrix compound composed of [ZnCl 4 ] 2− tetragonal vertices is shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The r Mn2+ = 0.80 Å is very close to the r Zn2+ = 0.74 Å, which indicates the possible substitution of Zn 2+ ions in the lattice of Cs 12 Zn 4 Cl 20 . [ 19,20 ] Compared to the XRD pattern of undoped sample, the diffraction peaks are slightly skewed to the smaller angle side, which may be due to the introduction of Mn 2+ ions into the lattice. [ 16,21,22 ] The typical Cs 12 Zn 4 Cl 20 matrix compound composed of [ZnCl 4 ] 2− tetragonal vertices is shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…These results not only provide an effective approach for the preparation of new perovskite structure but also provide some new ideas for the practical applications of perovskite crystal materials in the field of LEDs. [19,20] Compared to the XRD pattern of undoped sample, the diffraction peaks are slightly skewed to the smaller angle side, which may be due to the introduction of Mn 2þ ions into the lattice. [16,21,22] The typical Cs 12 Zn 4 Cl 20 matrix compound composed of [ZnCl 4 ] 2À tetragonal vertices is shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…CsPbCl 3 NCs gradually lose the PL intensity during 4 days of water stability test (Figure d and black squares in Figure f), while CsPbCl 3 /CsMnCl 3 core/shell NCs still retain ∼88% of the original PL intensity after 15 days in water (Figure e and red dots in Figure f). The improved water stability of the CsPbCl 3 /CsMnCl 3 core/shell NCs is likely due to the great structural stability of CsMnCl 3 under ambient conditions and the improved stability of the core NCs after Mn 2+ dopant incorporation, as it was reported that doping into a perovskite lattice could significantly increase the structure stability of the host perovskite . The water stability of the CsMnCl 3 shell materials was tested by the XRD measurement of the CsMnCl 3 NCs after dispersion in water under continuous stirring (Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…Lead-free and tin-free PIMs typically show higher stability than lead perovskites under air exposure, humidity, and high temperatures. [49][50][51][52] Sansom et al reported that the XRD pattern of bulk AgBiI 4 sample remains unchanged up to 90 °C, above which a small quantity of Ag 2 BiI 5 started appearing as an impurity while the crystal structure of the film was still intact. 53 We investigated the structural and morphological stabilities of the AgBiI 4 NC films under ambient air exposure and heat treatment through XRD and SEM.…”
Section: Ambient and Thermal Stabilities Of Agbii 4 Ncsmentioning
confidence: 99%